العلماء الجزائريون في تونس ودورهم في الحياة العلمية والثقافية وأثرهم في التواصل الثقافي بين البلدين ما بين القرنين 16و19 م 10و13 هـ - البشير,مقدود (Universty Of El-oued جامعة الوادي, 2024)
تشكل بلاد المغرب وحدة طبيعية واحدة ولها امتداد روحي موحَد نظرا لاعتناق أهلها الإسلام منذ دخول الأفواج الأولى من الفاتحين المسلمين، والحديث عن تاريخ وحضارة بلد ـــ ماـــ لم يعد يقتصر على دراسة تاريخه السياسي وعلاقاته السياسية مع مختلف البلدان ،بل ترتقي إلى معرفة جوانبه المختلفة وعلاقاته الاجتماعية ،الاقتصادية والثقافية مع غيره من الشعوب، إن علاقة الجزائر العثمانية مع جيرانها تشمل جوانب مختلفة ومجالات عدة ،وقد تنوّعت أطرافها بحكم الموقع الاستراتيجي للجزائر فهي تمثّل قلب دول المغرب العربي ، ورغم علاقات التوتّر التي سادت بين الإيالتين في جانبها السياسي فإنّه لم يمنع هذا من حدوث علاقات ودِّية تمثّلت في وجود علاقات اقتصادية وأخرى ثقافية بينهما ، والتي تمثّلت في هجرة العلماء الجزائريين ومشاركتهم في الحياة العلمية والثقافية فكانت خير مظهر لهذه العلاقات وهذا التواصل بين المجتمعين والإيالتين خلال هذه الفترة . ومن أجل الوقوف على ذلك وتتبع المنحنى البياني لهجرة هؤلاء العلماء ومدى تأثيرهم في الحياة العامة وخاصة الثقافية منها في تونس كان اختياري لهذا الموضوع الموسوم ب "العلماء الجزائريون في تونس ودورهم في الحياة العلمية والثقافية وأثرهم في التواصل الثقافي بين البلدين ما بين القرنين 16و19م /10و13ه" ، وذلك من خلال طرح إشكالية عامة لهذا الموضوع وهي :ــ من هم العلماء الجزائريون الذين هاجروا نحو تونس خلال الفترة ما بين 16و19م ؟ وماهي العوامل المؤثّرة على هجرة هؤلاء العلماء وما هو دورهم في الحياة العلمية والثقافية في تونس. "؟ وقد عملت على تقسيم بحثي هذا إلى مقدّمة وفصل تمهيدي أو مدخل وأربعة فصول، وقد ختمت دراستي هذه بمجموعة من الملاحظات والاستنتاجات التي توصّلت إليها، والتي من أهمها :ـــ * تجذّر التواصل العلمي والثقافي بين الجزائر وتونس وهذا يعود لعوامل عدّة كان التاريخ والجغرافيا العامل الرئيسي فيها ،واستمراره رغم توتّر العلاقات السياسية أحيانا بينهما. * حظوة العلماء والرحالة الجزائريين في تونس وظهر ذلك من خلال التقدير والاحترام الذي قوبلوا به سواء من طرف الحكام أو حتى علماء تونس . The countries of the Maghreb constitute a single natural unit and have a unified spiritual extension due to its people’s embrace of Islam since the entry of the first groups of Muslim conquerors. Talking about the history and civilization of a country is no longer limited to studying its political history and political relations with various countries, but rather it rises to know its various aspects and social relations. Economic and cultural relations with other peoples. The relationship of Ottoman Algeria with its neighbors includes various aspects and many fields, and its parties were diversified due to the strategic location of Algeria, as it represents the heart of the countries of the Arab Maghreb. Despite the tensions that prevailed between the two provinces in its political aspect, they did not prevent the friendly relations from occurring which were represented by the existence of economic and cultural relations between them,and also the migration of Algerian scholars and their participation in scientific and cultural life, which was the best manifestation of these relations and this communication between the two societies and the two regions during this period. In order to determine this and follow the migration of these scholars and the extent of their influence on public life, especially cultural life, in Tunisia, I chose this topic entitled “Algerian scholars in Tunisia and their role in scientific and cultural life and their impact on cultural communication between the two countries between the 16th and 19th centuries AD / 10 and 13 AH.” This is done by presenting a general problem for this topic, which is: Who are the Algerian scholars who immigrated to Tunisia during the period between 16 and 19 AD? What are the factors affecting the migration of these scholars and what is their role in scientific and cultural life in Tunisia? I have divided my research into an introduction, an preliminary chapter or a preface and four chapters. I concluded my study with a set of observations and deductions that I reached, the most important of which are: History and Geography are considered, among others, the main factors that strengthened the scientific and cultural relations between them despite the tensional relations which sometimes occurred . The favor of Algerian scholars and travelers in Tunisia, and this was evident through the appreciation and respect with which they were met, whether by the rulers or even Tunisian scholars.
أطروحة دكتوراه تخصص التاريخ الحديث و المعاصر في العلوم الإنسانية و الإجتماعية
Keywords: الفترة العثمانية ــــ التواصل الثقافي ــــ العلماء الجزائريون ـــ المراكز العلمية ـــ الجزائر ـــ تونس ـــ الطرق الصوفية ــــ عوامل الهجرة ــ الإجازات العلمية .; the Ottoman period - cultural communication - Algerian scholars - scientific centers - Algeria - Tunisia - Sufi methods - factors of migration - academic licenses.